3D Structural Electronics Via Multi‐Directional Robot 3D Printing. Issue 5 (2nd December 2022) - Bao, Chao; Moeinnia, Hadi; Kim, Tae‐Ho; Lee, Wonchul; Kim, Woo Soo
Abstract: Multi‐material 3D printing is an innovative technology that sparks a revolution in combined structural 3D printing with different functional materials. However, current multi‐material printing systems work alone and cannot take full advantage of each printing, and the limited freedom of existing 3D printers confines diversity of structural designs. Here, a double‐arm robotic 3D printing system combined with paste‐based direct ink writing (DIW) and filament‐based fused filament fabrication (FFF) is reported as a new fabrication solution for customized 3D structural electronics. Collaboration between two robot arms brings about a spontaneous sintering effect of metal nano‐particles (minimum resistance = 14.5 Ω per 10 mm) by addition of the following extruded layer through FFF for the fabrication of embedded sensors, which reduces the post‐processing steps and saves energy for sintering compared with the conventional parallel multi‐material 3D printing processes. The extra freedom of motions from two robot‐arm 3D printing enables multi‐directional curvilinear printing for 3D structural electronics, such as a double‐helix‐shaped embedded sensor. In addition, precise robot motion enables the electrical registration and vertical integration of multi‐layered printed circuit boards. Establishment of new double‐robot 3D printing system expands design freedom and realization of 3D structural electronics. Abstract : A double‐robot‐based multi‐directional 3D printing technology is reported that not only contributes to multi‐material 3D printing but also ushers to the direction of curvilinear 3D printing through industrial six‐axis robots. Multi‐directional conductive 3D printing is demonstrated on the double‐helix structures as well as fabrication of multi‐layered printed circuit boards (PCBs).